Convergence Study for Rock Unconfined Compression Test Using Discrete Element Method - Shahrin, Muhammad Irfan; Abdullah, Rini Asnida; Alel, Mohd Nur Asmawisham; Saari, Radzuan; Ibrahim, Nurul Ain; Mat Yusof, Nur Ain; Abd Rashid, Mohd Fadhli (International Journal of Integrated Engineering, 2021)
Mesh convergence is a vital issue that needs to be addressed in a numerical model. This study investigated the effects of mesh element number on the Discrete Element Method (DEM) to granite rock response under compression loading. This study used the 3D finite-element code LS-DYNA to model the Unconfined Compression Test (UCT) numerical simulation. Models with five different mesh types were conducted for convergence mesh, namely normal mesh, fine mesh, super fine mesh, coarse mesh, and super coarse mesh. The mesh convergence of rock media has been conducted using DEM and steel plates simulated using the Finite Element Method (FEM). The DEM-FEM numerical analysis is compared with the results obtained from the experimental test. The best mesh was obtained as the simulation could reproduce the stress-strain curve trends, the failure behaviour and compression strength observed in the experimental test. The normal mesh was selected as the best mesh type in this study based on the comparisons that have been made. This study shows that the DEM-FEM numerical simulation can represent granite rock and can be used for further study based on mesh convergence.